2018
DOI: 10.1038/s41467-018-04769-6
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable near white-emissive two-dimensional covalent organic frameworks

Abstract: Most two-dimensional (2D) covalent organic frameworks (COFs) are non-fluorescent in the solid state even when they are constructed from emissive building blocks. The fluorescence quenching is usually attributed to non-irradiative rotation-related or π–π stacking-caused thermal energy dissipation process. Currently there is a lack of guiding principle on how to design fluorescent, solid-state material made of COF. Herein, we demonstrate that the eclipsed stacking structure of 2D COFs can be used to turn on, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
186
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(203 citation statements)
references
References 50 publications
7
186
0
Order By: Relevance
“…128 Reducing the number of or deepening the minima in the stacking landscape are therefore approaches to improve the crystallinity in COFs. To this end, other, more directional inter-layer forces such as hydrogen bonding 180 or well-designed dipole-dipole interactions have been employed to enhance the order of interlayer stacking. The design of weak interlayer interactions to improve the crystallization is much more challenging than the intralayer structure, as the exact stacking configuration is highly dependent on factors such as the shape of the building blocks.…”
Section: Review Articlementioning
confidence: 99%
“…128 Reducing the number of or deepening the minima in the stacking landscape are therefore approaches to improve the crystallinity in COFs. To this end, other, more directional inter-layer forces such as hydrogen bonding 180 or well-designed dipole-dipole interactions have been employed to enhance the order of interlayer stacking. The design of weak interlayer interactions to improve the crystallization is much more challenging than the intralayer structure, as the exact stacking configuration is highly dependent on factors such as the shape of the building blocks.…”
Section: Review Articlementioning
confidence: 99%
“…In this regard, COFs are among the most difficult to crystallise, owing to the lesser reversibility of their covalent linkages compared to coordination bonds and hydrogen bonds in MOFs and HOFs. The ease of encoding functionalities in COFs and their structural robustness render them potentially useful in wide-ranging applications [13][14][15][16][17][18][19] . However, an in-depth understanding of the structure-property correlation in COFs is lacking, owing to the fact that most synthesised COFs are polycrystalline, which hampers structural determination.…”
mentioning
confidence: 99%
“…15,16 However, interlayer hydrogen bonding in COFs is much rarer. There are only a few examples of hydrazone 17,18 or urea 12 containing COFs where interlayer hydrogen bonding is observed or predicted, reported in literature. Several COFs have been reported that have interlayer C-H⋯O, and C-H⋯N hydrogen bonding through sidechain interactions, 13,14,19 however, more canonical N-H⋯O hydrogen bonding interactions similar to those found between amide groups found in Nature, or in synthetic polymers such as Kevlar or Nylon, are much rarer.…”
mentioning
confidence: 99%